MATHEMATICAL MIXER MODEL WITH FORMATION OF HETERODYNE ANTIPHASE SIGNAL - z. N. Mirzaev; M. S. Guseynov; T. G. Aigumov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives To carry out calculations involved in the design of a microwave mixer with a diplexer with the formation of the antiphase heterodyne signal using a slot resonator.Method In order to calculate and optimise the characteristics, design and topological parameters of microwave mixers, the results of the design bandpass filter  PF and low-pass filter (LPF) mixers of through-feed type were used. The characteristics of mixers and their structural elements were calculated using the Serenade software package intended for the automated calculation of microwave devices. A distinct feature of designing mixers (with a diplexer) involves the need to optimise the topology of the diplexer before optimising the mixer characteristics.Results The characteristics of nonlinear distortions show that the maximum power level at the mixer inlet should not exceed -15 – -20 dBm. In order to attenuate the intermodulation distortions of the 3rd order, this level should be higher that 50 dBs. The relatively low level of compression and suppression of harmonic and intermodulation distortions associated with the minimisation of the heterodyne power level at the calculation of characteristics of mixers of the required heterodyne power level (Rh ~ 5-7 dBm) is due to the minimum expenses at the realisation of sources of heterodyne signals. A noticeable improvement in the characteristics of mixers by nonlinear distortions can be achieved by shifting the operating point at the points on the current-voltage characteristic (VAC) diodes by an external voltage source with a simultaneous increase in Ph by several dB (up to Ph = 10 dBm).Conclusion A mode of increased nonlinear distortion suppression can be practically realised by switching on diodes through resistive-capacitive circuits (auto-shift) or using diodes with an increased potential barrier. The calculation shows that it is possible to realise sufficiently small conversion losses of 6.6-8.0 dB at low levels of Rh ~ 5-7 dBm.